International Monetary Fund Annual Report 2013 : Promoting a More Secure and Stable Global Economy. - International Monetary Fund. Secretary's Department (Washington, D.C. : International Monetary Fund, 2014)
The IMF's 2013 Annual Report chronicles the response of the institution's Executive Board and staff to the global financial crisis and other events during financial year 2013, which covers the period from May 1, 2012, through April 30, 2013. The print version of the report is available in eight languages (Arabic, Chinese, English, French, German, Japanese, Russian, and Spanish), along with a CD-ROM (available in English only) that includes the report text and ancillary materials, including the IMF's Financial Statements for FY2013.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet